Perbaikan Manajemen Pemeliharaan dalam Rangka Mendukung Pembibitan Kambing Kacang bagi Warga di Kecamatan Bone Pantai Kabupaten Bone Bolango - Fahrul Ilham; Muhammad Mukhtar (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2018)
The purpose of this Community Service Program is to provide knowledges and skills for the community in Bone Pantai Sub district about the goat raising to support the animal breeding program by improving the maintenance management. This activities have been implemented on the livestock herders of Kacang goat which is located in Lembah Hijau Village and Tolotio Village, Bone Pantai Sub District, Bone Bolango Distric. The method used in conducting the community empowerment is giving the teory and simulation upon the community members and continuing with practice directly in the field. Program activities that have been implemented are: the goat house making, goats selection, silage making, feeding, injection prostaglandin F2α (PGF2α), prevention and treatment of the sick goats, and organic fertilizer making. Based on the result and discussion, it is concluded that the program of kacang goat breeding is an important step in order to maintain its purity and sustainability. The support program activities that can be done are: management improvement of the maintenance and housing, selection of prospective does and bucks, appropriate feeding as the the goats need, application of reproductive technology by modification of the hormonal system, prevention and treatment of the disease routinely, and recycling the manure into organic fertilizer. To make the programs sustainable, it is necessary to build communication network between the farmers and government and the industry so that the products of kacang goat breeding programs can be marketed and provide economic value for the community in Kecamatan Bone Pantai.